Informed consent in research ethics: an analysis from the perspective of Luhmann's social systems theory. Issue 3 (August 2018) - Burr, Jennifer; Gibson, Barry
Abstract We explore the origins and dynamics of ethical communication with reference to the requirements for informed consent provision in research ethics. We adopt the analytical framework developed in Luhmann's social systems theory to illustrate how ethical communication about informed consent has developed in the medical, legal and scientific systems. We would like to suggest that the development of ethical communication is the result of the developing semantics of individuality and personhood. Our analysis adds specific observations about how communication about research ethics, and informed consent specifically, reduces complexity in an increasingly functionally differentiated society.